"Cric, crac, queer": queer storytellers and story-membering in Lawrence Scott's Witchbroom, Shani Mootoo's Cereus Blooms at Night and David Chariandy's Brother. Issue 2 (4th May 2021) - Bomans, Bastien
ABSTRACT: In the field of Caribbean literature, the figure of the storyteller is commonly associated with an ethos of resistance against the racist and sexist representations of the colonial version of history. Furthermore, some creative writers have turned to this emblematic character to highlight the existence of Caribbean LGBTQI+ identities. In this article, I explore three novels that present such queer storytellers: the intersex character Lavren in Lawrence Scott's Witchbroom (1992), the transgender woman Tyler in Shani Mootoo's Cereus Blooms at Night (1996) and the "gay" man Jelly in David Chariandy's Brother (2017). By queering storytelling, these writers draw attention to the imbrications of systems of oppression, and to the empathetic bonds that can potentially be created between oppressed individuals. Without occluding the possibility of unreliability that characterizes human subjectivity, the queer storyteller becomes a reconciliatory figure who offers alternative visions of the past, of the present and of the future.